Cyclic sealing and drainage on an oceanic transform fault - Hao Yang; Lingling Ye; Haijiang Zhang (Science, 2026)
Oceanic transform faults have been considered conservative, shear-dominated boundaries, yet their proximity to magmatic systems implies fluid involvement. In this work, we discovered tidally modulated tremor at the Gofar transform fault along the East Pacific Rise. Tremor amplitude correlates with semidiurnal tides during periods of sparse seismicity and low in situ compressional to shear wave velocity ratio ( V p/ V s), but this correlation weakens following earthquake swarms accompanied by high V p/ V s. We propose a valve-like sealing-drainage dynamic process where sealing traps volatiles and boosts tidal sensitivity, sustaining tremor activity until rupture opens high porosity and permeability pathways, which silences tremors, triggers microseismicity, and resets the system through hydrothermal resealing. Thus, transform faults are likely permeable and tide critical, with energy release oscillating between tremors and rupture, paced by magmatic volatile supply and healing.